The Andalite's gift - Applegate, Katherine (New York : Scholastic, 1997)
The Animorphs needed a break from the superhero stuff and everything should have been cool. But Rachel is missing and something is after the kids.
"An Apple paperback.".
Keywords: Science fiction; Science fiction